2007
DOI: 10.3201/eid1306.061264
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Reduce Person-to-Person Transmission during WidespreadEscherichia coliO157:H7 Outbreak

Abstract: RESEARCHDuring the Escherichia coli O157:H7 outbreak in 2006 in the United States, the primary strategy to prevent illness was to advise consumers not to eat spinach. No widespread warnings were issued about preventing person-to-person (secondary) transmission. A disease transmission model, fi tted to the current data, was used to investigate likely reductions in illnesses that could result from interventions to prevent secondary transmission. The model indicates that exposure to contaminated spinach occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 30 publications
(32 reference statements)
2
35
0
3
Order By: Relevance
“…Person-to-person transmission of EHEC may contribute to outbreaks from a primary source (Parry et al, 1998;Seto et al, 2007) and may reach 14% (Rangel et al, 2005) or higher; secondary cases occurred in 20=89 households with STEC O157 infection in the United Kingdom , and significant interpersonal spread was noted in 18-case O157 outbreak in Ireland, with identical=close PFGE patterns in isolates from patients and a rectal animal swab (Mannix et al,…”
Section: Direct Transmissionmentioning
confidence: 99%
“…Person-to-person transmission of EHEC may contribute to outbreaks from a primary source (Parry et al, 1998;Seto et al, 2007) and may reach 14% (Rangel et al, 2005) or higher; secondary cases occurred in 20=89 households with STEC O157 infection in the United Kingdom , and significant interpersonal spread was noted in 18-case O157 outbreak in Ireland, with identical=close PFGE patterns in isolates from patients and a rectal animal swab (Mannix et al,…”
Section: Direct Transmissionmentioning
confidence: 99%
“…serotype etiologically associated with HUS is generally believed to be O157:H7, such as what was observed in the STEC outbreak in the fall of 2006 in USA which was induced by contaminated spinach, and in the large-scale epidemic that happened in China in 1999-2000 (Seto et al, 2007). However, an unusual E. coli serotype O104:H4 was identified to be responsible for German STEC outbreak in 2011, which caused thousands of infection and HUS cases, demonstrating horizontal gene exchange event during enterobacteria natural evolution (Bezuidt et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Modelling may also permit assessment of combined intervention strategies, which more closely reflects real-world situations. Based on data from previous outbreaks, studies have used models to simulate the expected temporal distribution of cases (epidemic curve) and quantify the effect of interventions (3,4).…”
Section: Data Limitations and Implications For Future Researchmentioning
confidence: 99%
“…Outbreak data have also been used to assess the impact of interventions. Seto et al (2007) used data from a multistate outbreak of Escherichia coli O157:H7 in the United States to model control strategies and found that reducing secondary transmission by 1-25% could prevent 2-3% of secondary cases and 5-11% of infected and symptomatic individuals (3). Chen et al (2014) used data from a waterborne shigellosis outbreak at a school in China to examine the effect and optimal combination of five interventions on the attack rate and outbreak duration (4).…”
Section: Introductionmentioning
confidence: 99%